2019
DOI: 10.3390/mi10040276
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cigarette Smoke Using a Surface-Acoustic-Wave Gas Sensor with Non-Polymer-Based Oxidized Hollow Mesoporous Carbon Nanospheres

Abstract: The objective of this research was to develop a surface-acoustic-wave (SAW) sensor of cigarette smoke to prevent tobacco hazards and to detect cigarette smoke in real time through the adsorption of an ambient tobacco marker. The SAW sensor was coated with oxidized hollow mesoporous carbon nanospheres (O-HMC) as a sensing material of a new type, which replaced a polymer. O-HMC were fabricated using nitric acid to form carboxyl groups on carbon frameworks. The modified conditions of O-HMC were analyzed with Scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…This is a huge leap when compared to traditional diffusion-onlybased systems that would take about an hour for the same level of detection. Cheng et al used oxidized hollow mesoporous carbon nanospheres (O-HMC) coated on a SAW sensor (figure 2(b)) [58]. This material achieved a sensitivity of 51.2 Hz ppm −1 to a standard tobacco marker (3ethenylpyridine, 3-EP), which was a significant improvement compared to the 37.8 Hz ppm −1 sensitivity of the polyacrylic acid and hollow mesoporous carbon nanospheres (PAA-HMC).…”
Section: Gas Sensors Specially Designed For Tobacco Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a huge leap when compared to traditional diffusion-onlybased systems that would take about an hour for the same level of detection. Cheng et al used oxidized hollow mesoporous carbon nanospheres (O-HMC) coated on a SAW sensor (figure 2(b)) [58]. This material achieved a sensitivity of 51.2 Hz ppm −1 to a standard tobacco marker (3ethenylpyridine, 3-EP), which was a significant improvement compared to the 37.8 Hz ppm −1 sensitivity of the polyacrylic acid and hollow mesoporous carbon nanospheres (PAA-HMC).…”
Section: Gas Sensors Specially Designed For Tobacco Applicationsmentioning
confidence: 99%
“…The most powerful to combat this challenge is using filter. Cheng et al reported that to prevent tar adhesion, particles above 1 µm are filtered [58]. This allows the SAW sensor to detect cigarette smoke with sufficient sensitivity and satisfactory repeatability.…”
Section: Sensor Drift and Calibrationmentioning
confidence: 99%
“…Though there are some technologies to detect smoke, among which the surface acoustic wave sensor for the third-hand smoke [1,2], the passive detection method for smoking cessation [3], and smoke detection method for aircraft cargo compartment [4] have caught much attention. This paper suggests an economic and effective smoke sensor made of fabrics with a simple surface treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Eight papers are published in this special issue and cover the design of microfluidics for bioseparation [1,2,3,4,5,6], incorporation of sensors with microfluidics for particle detection [6,7], and modular devices with both functions [1,6,7]. Nanomaterials have been combined with microfluidics for both separation [5] and sensing [7] purposes. The special issue also includes a review on programmable paper-based microfluidics [8].…”
mentioning
confidence: 99%
“…Yang et al [6] took advantage of particle inertia in curved microfluidic channels to separate and contain particles in micro-tanks, which were further resolved by optical diffraction. Cheng et al [7] coated a surface acoustic wave sensor with oxidized mesoporous carbon nanospheres to trap chemical compounds in smoke, where the coating increased the sensitivity and selectivity of the acoustic wave sensor. Boltz et al [1] designed a split-flow device to perform continuous, in-line quality control of nanoparticle synthesis.…”
mentioning
confidence: 99%